City Development Strategy : Colombo - Municipal Council of Colombo (Colombo, Sri Lanka, 2014)
The Colombo Municipal Council (CMC), in collaboration with the World Bank, UNDP, UNCHS (HABITAT) and the Western Provincial Council (WPC) in Sri Lanka, launched a project in February 2000 to formulate a comprehensive strategy framework and a perspective plan of action for development of the city. The purpose was to identify key areas and issues that need systemic and planned attention of the Council and other major stakeholders and to develop appropriate strategies to address them. A Senior Consultant was assigned to the CMC by the sponsors to help formulate the strategy through a consultative process. In formulating the strategy framework, the CMC consulted a wide variety of stakeholder groups through a series of formal and informal consultations. They included civil society partners such as NGOs and CBOs, representatives of the poor; senior municipal officials; and leading private sector representatives, i.e., major investors, realtors, developers and Chambers of Commerce & Industry. Their views, ideas and suggestions were reviewed and those compatible with the development vision and thrust identified by the CMC task forces and stakeholder consultations are incorporated in this strategy framework. All stakeholders, particularly the private sector, considered the opportunity as an unprecedented move by the CMC and WPC. They welcomed the offer to join in this unique partnership-building exercise in city management and have assured the city administration of their wholehearted cooperation.